A Novel Thermoresponsive Catalytic Membrane with Multiscale Pores Prepared via Vapor‐Induced Phase Separation. Issue 18 (3rd April 2018) - Xie, Rui; Luo, Feng; Zhang, Lei; Guo, Shi‐Fei; Liu, Zhuang; Ju, Xiao‐Jie; Wang, Wei; Chu, Liang‐Yin
Abstract: A novel thermoresponsive catalytic polyethersulfone membrane with multiscale pores is developed by constructing silver nanoparticles (Ag NPs) loaded poly( N ‐isopropylacrylamide) (PNIPAM) nanogels on pore walls of cellular pores as thermoresponsive gates and catalysts via vapor‐induced phase separation. The Ag NPs are stably immobilized on the PNIPAM nanogels by an in situ reduction method based on the versatile adhesion and reduction properties of polydopamine. The micrometer cellular pores decorated with Ag NPs loaded PNIPAM nanogels are formed throughout the membrane and act as numerous microreactors with a large pore surface. The proposed membrane exhibits both satisfactory thermoresponsive characteristics and stable catalytic properties. The effects of operation temperature and reactant concentration of feed solution on the catalytic properties are investigated systematically. The results show that the apparent kinetic rate constant of catalytic reduction of 4‐nitrophenol (4‐NP) in water by reductant sodium borohydride (NaBH4 ), is ranging from 3.7 to 37.9 min ‐1 at temperatures from 20 to 45 ºC and the molar ratio of NaBH4 to 4‐NP from 100:1 to 500:1. When the reactant concentration in feed solution fluctuates, the permeability or throughput of the membrane is simply adjusted by virtue of the thermoresponsive characteristics of membranes to achieve high catalytic conversion of reactant. Abstract : A novel thermoresponsive catalytic membrane with thermoresponsive nanogels containing silver nanocatalysts embedded on the walls of cellular pores is designed and developed. The as‐prepared membrane achieves the optimal throughput for different capacities, and simultaneously retains high conversion of the catalytic reaction. Thus, a membrane‐based smart catalytic process with high efficiency is successfully achieved.